MODEL KEMITRAAN PKBM, DUNIA INDUSTRI, DAN PEMERINTAH UNTUK PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PENDIDIKAN KEWIRAUSAHAAN - Hakim, Asep Abdurrahman; Ansori, Ansori; Nuraeni, Lenny (Jurusan Pendidikan Masyarakat Fakultas Keguruan Ilmu Pendidikan Universitas Siliwangi, 2025)
Strategic partnerships among Community Learning Centers (PKBM), industries, and governments play a critical role in empowering community economies through entrepreneurship education. This study aims to identify and develop an effective collaborative model that integrates multiparty efforts to support entrepreneurship training based on local needs. The research employed a qualitative-descriptive method with a case study approach at PKBM Attarbiyah, Arjasari District, Bandung Regency. Data were collected through in-depth interviews, observations, and document analysis. The findings reveal that collaboration involving industries in providing technology-based training, government support through policies and regulations, and PKBM as program facilitators effectively enhances learners' entrepreneurial skills and strengthens local economic ecosystems. This model resulted in a 40% increase in learners' economic independence through training tailored to local industrial demands. The implementation of this model underscores the importance of multiparty synergy in ensuring the sustainability of entrepreneurship education. These findings support the development of policies and practices in community education aligned with the goals of community-based economic empowerment.